Modelling of local mechanical failures in solid oxide cell stacks. (1st July 2021) - Miao, Xing-Yuan; Rizvandi, Omid Babaie; Navasa, Maria; Frandsen, Henrik Lund
Abstract: Solid oxide cells can deliver highly efficient energy conversions between electricity and fuels/chemicals. A central challenge of upscaling solid oxide cells is the probability of failure of the brittle ceramic components. The failures of the ceramic components may lead to significant degradation or eventual failure of a stack. To predict mechanical failures in a stack, a full stack model is needed, together with a local assessment of stresses at the vicinity of failing regions, e.g. the contact points between the cells and interconnects. A conventional three-dimensional model requires a very fine discretization of the mesh to capture stress intensities. Computational resources needed for such a model are therefore immense, and it is highly unlikely to compute at stack scale, as well describe the evolution over time. In this work, the homogenization modelling framework for solid oxide cell stacks is extended to identify local mechanical failures. Thus, the fracturing within a local failing point is examined by using a localization approach, where stresses in the stack model are linked to the local stresses and the energy release rate at the crack tip of the relevant interface. This is done in a general manner, such that the local stresses and the energy release rate can be evaluated at every point in the stack at every instant of time without loss of computational efficiency. A 100-cell stack can be modelled in three dimensions with all coupled multiphysics in steady state within 3 min on a current workstation computer. Highlights: Local mechanical failures in a fuel cell stack are modelled for the first time. This is made possible by using a novel multiscale multiphysics modelling approach. The impact of stack design and flows on local mechanical failures are modelled. Exceptional computing speed achieved: 100-cell stack in 3 minutes for steady-state.